PENGARUH PANDEMI VIRUS CORONA (COVID-19) TERHADAP PENDAPATAN PEDAGANG SAYUR DAN BUAH DI PASAR TRADISIONAL “PAJAK PAGI PASAR V” PADANG BULAN - Robert Sinaga; Melfrianti Romauli Purba (JURNAL REGIONOMIC, 2020)
The object of this research was to determine the pandemic Covid-19 impact on the income of fruits and vegetables traders in the Traditional Market “Pajak Pagi Pasar V Padang Bulan Medan. The research was conducted using qualitative descriptive analysis methods by describing and interpreting data as well as the conditions or phenomena. From the research that has been carried out, it had been obtained that the responden continue their business in the market during the pandemic, even the number of buyers and incomehad decrease more than 50%. Factor that made traders continue doing business was the awareness and struggle to meet the needs of daily life. Meanwhile the inhibitng factors are the reduction in the number of buyers, income that had been decreased about more than 50% and worries about being exposed to the virus.